Exploring Students’ Learning Obstacles in Understanding Rational and Irrational Numbers: A Qualitative Study - Diana, Nanang (Al-Mufid, 2024)
This study aims to identify and analyze the learning obstacles encountered by students in understanding the concepts of rational and irrational numbers. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving eighth-grade students at a junior high school. The findings reveal three predominant types of obstacles: epistemological, ontogenic, and didactical. Epistemological obstacles are evident in students’ misconceptions regarding irrational numbers, particularly in interpreting them as recurring decimals. Ontogenic obstacles stem from students’ limited prior experiences, especially in connecting fractional concepts with square roots. Meanwhile, didactical obstacles relate to instructional approaches that fail to bridge students’ conceptual understanding. These findings underscore the need for learning designs that align with students’ cognitive structures and incorporate visual representations to facilitate comprehension of rational and irrational number concepts. The study recommends the adoption of constructivist-based instructional strategies to minimize such learning obstacles.